Preformulation studies on partially pregelatinized starch prepared from cassava Manihot esculenta Crantz (Family Euphorbiaceae) - Nadales, Gerlie
Modified starches are commonly used as binder and disintegrants to tablets prepared by direct compression. The objective of this study is to modify Cassava starch by partial pregelatinization as well as perform preformulation studies to this product.